Clinical Significance of Portal Hypertension Diagnosed With Bedside Ultrasound After Cardiac Surgery. (April 2017) - Denault, André Y.; Beaubien-Souligny, William; Elmi-Sarabi, Mahsa; Eljaiek, Roberto; El-Hamamsy, Ismail; Lamarche, Yoan; Chronopoulos, Alexandra; Lambert, Jean; Bouchard, Josée; Desjardins, Georges
Abstract : BACKGROUND: Portal venous flow pulsatility detected by Doppler ultrasound is a sign of congestive heart failure in noncritically ill patients. The assessment of portal and splenic venous flows has never been reported in patients undergoing cardiac surgery. METHODS: This is a case series performed in patients undergoing cardiac surgery between February 2014 and February 2015 in which portal and/or splenic venous flows were assessed by the attending anesthesiologist during surgery or by the intensivist after surgery using transthoracic echography in 9 patients or transesophageal echocardiography in 5 patients. Data collection was done retrospectively by reviewing intraoperative and postoperative monitoring documents. The technique of assessment is detailed in this article. RESULTS: We report the abnormal portal and/or splenic venous flow pulsatility from 14 patients perioperatively. At the time of pulsatility detection, patients had a median cumulative fluid balance of 3.8 L (interquartile range: 0–4.6 L) and a median right atrial pressure of 14.0 mm Hg (interquartile range: 12.0–15.5 mm Hg). In some patients (4/14), signs of right ventricular dysfunction on echocardiography and/or right ventricular pressure monitoring were present. CONCLUSIONS: Doppler evaluation of portal and splenic venous flow using transthoracic echography and transesophageal echocardiography may represent a promising modality to assess end-organ venous congestion in cardiac surgery patients. Abstract : Published ahead of print Febraury 2, 2017.